2013
DOI: 10.1007/s00221-013-3470-z
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of light touch sensory cues to corrective reactions during treadmill locomotion

Abstract: The arms play an important role in balance regulation during walking. In general, perturbations delivered during walking trigger whole-body corrective responses. For instance, holding to stable handles can largely attenuate and even suppress responses in the leg muscles to perturbations during walking. Particular attention has been given to the influence of light touch on postural control. During standing, lightly touching a stable contact greatly reduces body sway and enhances corrective responses to postural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The increased muscle activity during normal walking may also be due to the change in the attentional demands as proposed above [22] but research investigating the effect of an added task on muscle activity during walking has shown mixed results [ 23 , 24 , 25 ]. Previous studies investigating the effect of added haptic input have also found mixed results for changes in muscle activity [ 7 , 10 , 26 , 27 ]; however, those studies were completed using treadmill walking[ 10 , 26 , 27 ], and/or with individuals who have had a stroke [ 7 , 27 ]. The absence of a significant difference in muscle activity with added touch for the tandem and balance beam conditions could be due to increased muscular requirements for the more difficult walking tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The increased muscle activity during normal walking may also be due to the change in the attentional demands as proposed above [22] but research investigating the effect of an added task on muscle activity during walking has shown mixed results [ 23 , 24 , 25 ]. Previous studies investigating the effect of added haptic input have also found mixed results for changes in muscle activity [ 7 , 10 , 26 , 27 ]; however, those studies were completed using treadmill walking[ 10 , 26 , 27 ], and/or with individuals who have had a stroke [ 7 , 27 ]. The absence of a significant difference in muscle activity with added touch for the tandem and balance beam conditions could be due to increased muscular requirements for the more difficult walking tasks.…”
Section: Discussionmentioning
confidence: 99%
“…This light touch effect is produced by cutaneous receptors sensing small differences in shear forces through skin deformation 5, 25 and it substantially increases postural stability on firm supports during quiet standing and after a perturbation to balance 8, 2527 . It has also been shown to improve gait efficiency by reducing muscle activity in the lower leg during treadmill walking before and after a gait perturbation 28 . However, no study has assessed if it is beneficial in environments where participants are exposed simultaneously to challenging physical and visual environments, and where the structures available for the provision of tactile information are highly flexible.…”
Section: Introductionmentioning
confidence: 99%
“…Subjects performed the active perceptual task as they walked while lightly touching (<2N, enforced with verbal feedback) an instrumented handrail located in front of the treadmill. This was done to ensure that individuals would maintain their position on the treadmill while walking with the virtual reality headset 34 . Recall that the Short-MidSpeed and Long-MidSpeed groups performed the step length tasks at a mid-walking speed (1.0 m/s), whereas the Short-SlowSpeed group performed the step length tasks at a slow walking speed (0.5 m/s).…”
Section: Methodsmentioning
confidence: 99%